PENGARUH PENDIDIKAN, KESEHATAN, INVESTASI PEMERINTAH, DAN INVESTASI SWASTA TERHADAP PRODUKTIVITAS TENAGA KERJA DI INDONESIA (Universitas PGRI Sumatera Barat, 2014)
This research aims to identify and analyze the effect of education, health, government investment and private investment on labor productivity in Indonesia. The results of the research find that the education, health, government investment and private investment give significant effect simultaneously and partially on labor productivity in Indonesia. The higher funding for education, health, high government investment, the increasing number of private investment will be invested in Indonesia and higher labor productivity in Indonesia. Policy implications of this research is, in an effort to increase the productivity of labor in Indonesia, the policies that must be taken by the government is more concerned with education and health by increasing financing for the improvement of the quality of human resources